RESPON REPRODUKSI INDUK BETINA SEPAT SIAM Trichogaster pectoralis TERHADAP PENAMBAHAN BAHAN SUPLEMEN DAN IMBUHAN PAKAN - Siswanto Siswanto; Untung Bijaksana; Indira Fitriliyani (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
The problem of the breeding of the snakeskin gouramy management was theinsufficient maximum degree of hatching eggs which only reached 80.03 %. One of the ways to overcome the problem was to improve the quality of eggs through the improvement of quality of feed given to the mothers of snakeskin gouramy withsupplements and food additives. This study aimed to evaluate the reproductive response of female snakeskin gouramy against the addition of supplements and feed additive, suchas: fish oil, vitamin E and extracts of ginger. The tested fish was female snakeskin gouramy with a minimum age of 8 months and were at maturity level of TKG I or TKGII. The Food used in this study were 3 kinds of commercial feed with the addition of vegetable oil (FCO), the feed with the addition of fish oil and vitamin E (FOT) and the feed with the addition of fish oil, vitamin E and extracts of ginger (FOTG).The results showed that FOT and FOTG could produce gonadosomatic index (GSI), fecundity, egg diameter, hatching eggs and survival rate better than the FCO feed.This occured presumably because of the effect of the addition of vitamin E that prevent edoxidation of fatty acids, so that fat could be used completely. As a result, the quality and quantity of eggs increased. GSI value on all treatments ranged from 3.07 to 3.57 %,fecundity ranged between 3,875 to 5,355 grains, egg diameter ranged from 0.70 to 0.93mm, hatching ranged from 78.12 to 89.58 % and survival rate ranged between 51 to 83 % in all treatments. Food with the addition of fish oil and vitamin E could produce better diameter of eggs and survival rate, while feed with the addition of fish oil, vitamin E and extracts of ginger could generate value gonadosomatic index (GSI), fecundity and hatching eggs higher.